STUDY IN SILICO OF THIOUREA-DERIVED COMPOUNDS AS TYROSINE KINASE RECEPTOR INHIBITORS - Budi Mulyati; Sri Sutjiningtyas; Herlina (Universitas Airlangga, Campus C Mulyorejo, Surabaya, Indonesia, 2022)
Cancer is a disease caused by protein mutations, which cause cells to proliferate uncontrollably. Inhibiting the action of protein kinases is one method of preventing the signal that initiates the process of uncontrolled cell proliferation. This research aimed to determine the affinity of thiourea-derived compound ligands with the protein tyrosine kinase enzyme (PDB ID: 5LMA). The binding energy between each ligand and the tyrosine kinase receptor ranged from -87,62 to -95,26 kcal/mol. The percentage of ligand interactions varies above 80%. On the active site of the amino acid residues Leu 456, Leu 495, Ala 496, Ala 497, Arg 498, and Val 500, the tyrosine kinase enzyme binds to the ligands of thiourea-derived compounds via hydrogen, pi alkyl, and alkyl bonds. Pharmacokinetic, toxicity, and Lipinski regulation of thiourea-derived compounds yielded significant results as anticancer drug candidates.